2019
DOI: 10.1111/1759-7714.13213
|View full text |Cite
|
Sign up to set email alerts
|

New perspective to evaluate N1 staging: The peripheral lymph node metastasis status of non‐small cell lung cancer

Abstract: Background Lymph node (LN) metastasis status is the decision‐making basis for the surgical procedure and adjuvant therapy modalities. Fewer studies have previously focused on LN metastasis in N1 station, especially on peripheral lymph node (PLN) metastasis in N1 station. This study aimed to reveal the metastasis status of PLN of non‐small cell lung cancer (NSCLC), and investigate its effects on N staging. Methods We retrospectively evaluated a consecutive series of patients who underwent curative resection for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“… 12 Its prognosis is closely related to the timing of treatment, early detection and timely treatment can present a satisfactory effect. 13 It is believed that 14 NSCLC with different genotypes have different tendencies of lymph node metastasis, which has a great influence on the selection of treatment methods. Yang et al 15 believe that patients with lymph node metastasis and multiple-organ metastasis present poorer prognosis in terms of survival time, and a better understanding of lymph node metastasis can help clinicians better select treatment methods for NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Its prognosis is closely related to the timing of treatment, early detection and timely treatment can present a satisfactory effect. 13 It is believed that 14 NSCLC with different genotypes have different tendencies of lymph node metastasis, which has a great influence on the selection of treatment methods. Yang et al 15 believe that patients with lymph node metastasis and multiple-organ metastasis present poorer prognosis in terms of survival time, and a better understanding of lymph node metastasis can help clinicians better select treatment methods for NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the pathological stage may increase by 2.4% or 11% after a routine or careful pathological examination. [6,16] According to the reports in the literature, N1 definitions are found to be insufficient in the last lung TNM classification. Evaluations in the form of nN, LNR, and combinations of these among themselves and localization are reported to reflect the prognosis more successfully.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 12 ] There are studies reporting a better outcome of nNa than nNb. [ 6 , 7 , 17 ] In a study, the five-year survival rate was 67.6% in nNa group and 66.6% in nNb group. [ 20 ] In the same study, although there was a better survival tendency in nNa group, there was no significant difference between the groups (p=0.623).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations